The Internet filter farce: why blocking software doesn't—and can't—work as promised. - Nunberg, Geoffrey (American Prospect)
The writer discusses why Internet filtering software cannot work as promised. He considers reasons why filters might make one uneasy. He points out that in a corporate setting, they restrict employee privacy. With regard to parental restrictions on children's access to information, he asserts that a filtering program has no way of knowing exactly what speech it blocks and that the software firms are doing all they can to keep their customers in the dark. He notes that firms justify their secrecy by citing the need to protect their intellectual property and arguing that publication of the lists of blocked sites would allow children to bypass the filters and access inappropriate materials. However, he argues that their real fear in making the lists public is that it would expose the inadequacy of their software. He considers why filters fail and what should be done to improve them and hold their makers accountable to reasonable standards of public disclosure.